Retraction of the article: Zhuravleva M.V., Kukes V.G., Prokofiev A.B., Arkhipov V.V., Olefir Yu.V., Serebrova S.Yu., Sokolov A.V., Sychev D.A. Efficacy and safety of medicines: the value and opportunities of clinical pharmacology - article Editorial (Регуляторные исследования и экспертиза лекарственных средств, 2022)
.